Dua Puluh Lima Tahun Ketangguhan: Dampak Sosiokultural Berkelanjutan atas Tragedi 1998 terhadap Etnis Tionghoa-Kristen di Sarang, Rembang, Jawa Tengah - Nely Rahmawati Zaimah (Reformed Center for Religion and Society, 2023)
In the aftermath of the tumultuous events 1998, the Sarang Subdistrict in Indonesia experienced profound socio-cultural transformations. This study examines the lasting impacts of that unforgettable year on Sarang's Christian Chinese community, known for its strict religious culture, including numerous pesantrens and influential figures who shape its cultural identity. The study uses qualitative methods to conduct in-depth interviews with six Chinese individuals who have chosen Sarang as their residence. The goal is to explore the significant links between the 1998 tragedy and the transformation of the Chinese ethnic landscape. The study also investigates whether the psycho-cultural phenomenon of identity reconstruction and assimilation, as described by participants, plays a role in these changes. Thus, it offers insights into broader societal dynamics within the country.